2020
DOI: 10.1007/s00109-020-01959-y
|View full text |Cite
|
Sign up to set email alerts
|

The acidic tumor microenvironment drives a stem-like phenotype in melanoma cells

Abstract: Acidosis characterizes the microenvironment of most solid tumors and is considered a new hallmark of cancer. It is mainly caused by both “aerobic” and “anaerobic” glycolysis of differently adapted cancer cells, with the final product lactic acid being responsible of the extracellular acidification. Many evidences underline the role of extracellular acidosis in tumor progression. Among the different findings, we demonstrated that acidosis-exposed cancer cells are characterized by an epithelial-to-mesenchymal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 64 publications
0
62
0
Order By: Relevance
“…Recent studies reported that tumor cells adapt to long-term acidosis. Exposing tumor cells to low pH for 4 weeks or longer induced changes in protein expression and functional properties [ 33 36 ]. In order to analyze whether the changes in gene expression described above are the result of a short-term acidification (24 h) or can also be found in tumor cells chronically adapted to low pH, AT1 cells were kept for 11 passages (5 weeks) at pH 6.6.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported that tumor cells adapt to long-term acidosis. Exposing tumor cells to low pH for 4 weeks or longer induced changes in protein expression and functional properties [ 33 36 ]. In order to analyze whether the changes in gene expression described above are the result of a short-term acidification (24 h) or can also be found in tumor cells chronically adapted to low pH, AT1 cells were kept for 11 passages (5 weeks) at pH 6.6.…”
Section: Resultsmentioning
confidence: 99%
“…Snail-mediated increase in glucose uptake and lactate production was also shown for gastric cancer [ 137 ]. Regarding breast cancer, Kim with colleagues showed that Snail reprograms glucose metabolism by repressing phosphofructokinase PFKP which switches the glucose flux towards the pentose phosphate pathway [ 150 ]. Physiologically, this dynamic regulation of PFKP allows cancer cells to survive under metabolic stress.…”
Section: Epithelial–mesenchymal Transition (Emt) and Associated Mementioning
confidence: 99%
“…For example, rapid tumor growth creates a deficit of nutrients [ 151 ], mechanistic hypertension [ 152 ], and acidosis [ 153 , 154 ]. In turn, acidosis drives EMT and stem-like phenotype by inducing TGF-beta [ 52 ] and stem-cell markers [ 150 ]. Using MCF7 breast cancer cells as a model, Sadeghi with colleagues (Sadeghi et al, 2020) has shown that acidosis promoted a partial EMT, conferring the cells with phenotypic characteristics of both epithelial and mesenchymal cells.…”
Section: Epithelial–mesenchymal Transition (Emt) and Associated Mementioning
confidence: 99%
“…One of these characteristics are increased lactic acid production as a result of upregulated aerobic and anaerobic glycolysis. As a consequence, the extracellular tumor cell environment (pH 6.2–7.0), endosomes (pH 5.0–6.5) and lysosomes (pH 4.5–5) become more acidic than healthy tissues and blood (pH ~7.4) [ 76 , 100 , 101 ]. Based on these properties, some acid-sensitive linkers have been designed to facilitate tumor-specific drug release of CPP–drug conjugates ( Figure 5 ), which will be highlighted in the following paragraphs.…”
Section: Cpp–drug Conjugation Using Functionalized Linkersmentioning
confidence: 99%